The WTO and the Covid‐19 “Vaccine Apartheid”: Big Pharma and the Minefield of Patents - Stéphane Paquin; Kristine Plouffe-Malette (Politics and Governance, 2023)
Unequal access to vaccines for the Covid-19 pandemic, also referred to as “vaccine apartheid,” has marginalized low-income countries again. In October 2020, India and South Africa proposed a temporary waiver from certain provisions of the TRIPS Agreement for the prevention of Covid-19 at the World Trade Organization (WTO). An agreement was later reached in Geneva on June 17, 2022. The objective of this article is to analyze the negotiation and agreement reached at the WTO. This article explores the difficulties of creating international public good in the field of public health within the milieu of powerful actors, namely big pharmaceutical companies with vested interests. The central argument of this article is that this agreement alone will not solve the vaccine access problem for low-income countries. It is too restrictive, does not cover trade secrets and know-how, production capacity, availability of raw materials, and even adds new limitations that did not exist before. The best option to promote the production of quality vaccines in low-income countries is to share technology and know-how on a voluntary basis through production agreements. One way to facilitate the cooperation of large pharmaceutical corporation is to make it easier for low-income countries to use compulsory licenses. Simplifying the use of this mechanism could help encourage pharmaceutical companies to enter into voluntary licensing agreements.